Youth justice: a Canadian overview - Winterdyk, John (Oxford University Press, 2020)
"Balanced and comprehensive, Youth Justice is the only textbook that provides multiple, current perspectives on the Canadian youth justice system. Written by experts from across the country to offer a range of perspectives on the patterns, theories, and emerging topics related to youth justice—including a new chapter on racialized youth—this text blends empirical research with contemporary, critical analysis, while incorporating youth voices throughout."--